PENERAPAN STRATEGI THINKING ALOUD PAIR PROBLEM SOLVING DENGAN BANTUAN LEMBAR KERJA SISWA DALAM PEMBELAJARAN BIOLOGI DI KELAS VII SMP NEGERI 2 BATUSANGKAR - Efendi, Agusman; Asmendri, Asmendri; Delfita, Rina (Jurnal Pembelajaran MIPA, 2014)
The purpose of this study was to determine the outcomes of learning and problem solving ability of students to apply biological TAPPS strategy with the help of worksheets in biology learning in class VII SMP N 2 Batusangkar. The study was quasi experimental research. The population in this study were students of class VII SMP N 2 Batusangkar enrolled in the academic year 2012/2013, total of 6 classes. The samples in this study were students VII.2 as an experimental class, and class VII. 4 as the control class. The design of this study is randomized posttest Only Control Group Design. The instrument used in this study is the achievement test and observation sheets. The results showed that the results of learning and problem solving skills with biology students use this strategy better than conventional learning.Key words:Â TAPPS strategy, worksheet, biology learning , problem solving